Pengembangan Alat Ukur Potensi Solar Photovoltaic (SPV) Menggunakan Arduino - Amanda Khaira Perdana; Iswadi Hasyim Rosma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Utilization of solar energy system is one of the most promising renewable energy resources to meet the energy demand. This resource has been developed and utilized in many countries. Indonesia, as one of the tropical countries has been blessed with a huge amount of radiant energy from the sun during the whole year. However, the solar energy resource data is very limited. Therefore, the purpose of this article is to develop an automatic solar measurement to measure the potential of solar energy resource. The availability of solar energy resource data are the foundation of information for designing, utilizing and deploying of solar energy generation and technologies. The automatic solar measurement has been tested and found that it has capability to measure not only solar radiation data but also other related parameters such as air temperature and humidity with significant accuracy.Keywords—solar energy source, microcontroller Arduino, solar radiation, temperature, relative humidity